KOMUNIKASI PERSUASIF KOMUNITAS EARTH HOUR DALAM MEMBENTUK PERILAKU RAMAH LINGKUNGAN PADA MASYARAKAT DI KOTA PEKANBARU (Studi pada Aksi Rampok Sampah Di Car Free Day Jalan Diponegoro) - Trilis Marwuri; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Garbage is an important issue in urban environments are constantly faced in line with the growing of population and an increase in construction activity. The garbage problem in Pekanbaru city, particularly in the area of Car Free Day (CFD) Diponegoro street can’t be solved only with the janitor, but need public awareness for the hygiene environmental. Efforts made by the Earth Hour Pekanbaru Community with persuasive the public through the action of “Rampok Sampah”. This study aims to determine the credibility of a communicator, messages and media used by the Earth Hour Community to establish a friendly environment behaviour in society at Pekanbaru city. This study used a qualitative descriptive study. Informants consisted of four people who are the committees of Earth Hour Pekanbaru Community using purposive technique and five people which is a public in the area of CFD using accidental sampling technique. Data was collected by participant observation, deep interview and documentation. To achieve the validity of the data in this research, researchers used the participation of extension and triangulation. The results showed that the Earth Hour Pekanbaru Community has credibility as a communicator that expertness includes KUMBANG (Belajar Kumpul Bareng) discussion and training from Indonesia Earth Hour, family gathering, experience as an MC (Master of Ceremony) and the educational background of the environment and can be trusted and the members of the Earth Hour Pekanbaru Community implement a friendly environmentally behavior. The persuasive message Earth Hour Pekanbaru Community is using verbal messages include clarity, directness and accuracy as well as nonverbal messages using a tool (use the artifact) as costumes of a plastic bag monster and protected animals for example turtles, eagle, elephant, monkey and a panda. The media used by Earth Hour Pekanbaru are, first offline media, using the quotes, posters and merchandise such as T-shirts, by inserting messages friendly environmentally. Second are, used a social networks Facebook, Twitter and Instagram. Third, printed and online media, send press releases to Riau Pos and Tribun Pekanbaru. The last is used a radio in the form of advertising and talk shows on Radio Cendana, Persada, and Green Radio.Keywords : Persuasive Communication, Community, Earth Hour, Friendly Environmentally.